“I’m a Red River local”: rock climbing mobilities and community hospitalities - Rickly, J.M. (Sage, 2017)
With individuals continually on the move, mobility fosters constellations of places at which individuals collectively moor and perform community. By focusing on one climbing destination – the Red River Gorge – this paper works across scales to highlight the spatial politics of mobilizing hospitality. In so doing, it summarizes the ways hosting/guesting thresholds dissolve with the growth of particular rock climbing associated infrastructures and moves to examine the ways climbers performances of community result in the (semi-)privatization of public space and attempts at localization. Further, the paper highlights the ways mobility is employed to maintain a political voice from afar, as well as to forge “local” identities with The Red as place with distinct subcultural (in)hospitality practices. Hospitality practices affirm power relations, they communicate who is at “home” and who has the power in a particular space to extend hospitality. The decision to extend hospitality is not simply the difference between an ethical encounter and a conditional one; it takes place in the very performance of identity. Thus, integrating a mobilities perspective into hospitality studies further illuminates the spatial politics that are at play in an ethics of hospitality.